Many love : a memoir of polyamory and finding love(s) - Johnson, Sophie Lucido (Touchstone, 2018)
"Sophie Lucido Johnson gets a lot of questions when she tells people that she's polyamorous. Many Love is an intimate look at this often misunderstood practice: its history, its misconceptions, and Sophie's personal transformation from serial monogamist to proud polyamorist. After trying for years to emulate her boomer parents' forty-year and still-going-strong marriage, Sophie realized that maybe the love she was looking for was down a road less traveled. In this bold, illustrated memoir, she explores her sexuality, her values, and the versions of love our society accepts and practices. Along the way, she shares what it's like to play on Tinder side-by-side with your boyfriend, encounter--and surmount--many types of jealousy, learn the power of female friendship, and other amazing things that happened when she stopped looking for "the one." In a lot of ways, Many Love is Sophie's love letter to everyone she has ever cared for. Witty, insightful, and complete with illustrations, this debut provides a memorable glimpse into an unconventional life"--